3(2v+14)=-15v

Simple and best practice solution for 3(2v+14)=-15v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2v+14)=-15v equation:


Simplifying
3(2v + 14) = -15v

Reorder the terms:
3(14 + 2v) = -15v
(14 * 3 + 2v * 3) = -15v
(42 + 6v) = -15v

Solving
42 + 6v = -15v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '15v' to each side of the equation.
42 + 6v + 15v = -15v + 15v

Combine like terms: 6v + 15v = 21v
42 + 21v = -15v + 15v

Combine like terms: -15v + 15v = 0
42 + 21v = 0

Add '-42' to each side of the equation.
42 + -42 + 21v = 0 + -42

Combine like terms: 42 + -42 = 0
0 + 21v = 0 + -42
21v = 0 + -42

Combine like terms: 0 + -42 = -42
21v = -42

Divide each side by '21'.
v = -2

Simplifying
v = -2

See similar equations:

| y^2+11y+62=0 | | 3(3j+15)=-3(11-5j) | | -4(4w+20)-15=-6w+17+18 | | 3=3(2q-7) | | (98x+27)9+5x-1=6(x+23) | | 9(2k+1)=-4+19k | | -3(-14q-19)-15q=-16-8+18q | | 6+5[1+2(2X-5)]=6(X-6) | | w/7+9=3 | | 4-2x=-2 | | 37=5x-13 | | 3+14f=6-9(-3f-17) | | 7(2u+11)=11u+17 | | -5(-6-6d)=6(20d+20) | | 8n-21=6n+5 | | -33z+28z^2-28=0 | | 3x=3(x+6) | | 1/4(4x+8)=6(x-3) | | -6(6-12s)=6(-2+8s) | | -42.12=7.8t | | 5c+12-6= | | -x^2+6x+14=0 | | -20u+12.03=-18.5u-15.27-5.4u | | 3x+2(x+5)=4(x+6) | | 10(6t+1)-15=t-(t+4) | | 121-5x=13x+19 | | x^3+2x^2-x=o | | -13v-16.08=1.76+9.22-10.8v | | 6x-4y+11=0 | | 6r^2-7r-5=5 | | -(15r+15)=3(-4r+1) | | -3(-4x+2)=5(x-3) |

Equations solver categories